Неотложная помощь пострадавшим при основных видах острых отравлений на морских судах (лекция) - Зарицкая, Л.П. (Актуальні проблеми транспортної медицини, 2009)
В лекції приведені сучасні дані по питанням екстреної медицини – рекомендації, як надавати невідкладну медичну допомогу потерпілим та хворим на догоспітальному етапі, які найбільш часто трапляються при гострих отруєннях на морських суднах. Розглянути питання ретельного вивчення токсічної ситуації – причин, умов, обставин на місці події кожного випадку гострого отруєння. Викладені звичайні в клінічної практиці класифікація, симптоматика та програма негайних медичних заходів, які спрямовані на швидке знищення токсичного агента з організму в обмежених умовах діагностичних та лікувальних можливостей. Modern data are presented to lectures concerning emergency medicine recommendations about rendering of urgent medical aid by the victim and patients at a prehospital stage at most often meeting acute poisonings on sea courts. Расматриваются questions of careful studying of a toxic situation the reasons, conditions, circumstances on a scene of each case of a sharp poisoning. The classification standard in clinical practice, semiology and the program of the urgent medical actions directed on fast
removal of the toxic agent from an organism in limited conditions of diagnostic and medical possibilities are stated Questions of careful studying of a toxic situation
the reasons, conditions, circumstances on a scene of each case of an acute poisoning are considered. The classification standard in clinical practice, semiology and the program of the urgent medical actions directed on fast removal of the toxic agent from an organism in limited conditions of diagnostic and medical possibilities are stated.